Pengentasan Kemiskinan pada Masyarakat Pertambakan sebagai Upaya Pengembangan Kawasan Strategis Agropolitan (Studi di Kecamatan Jabon Kabupaten Sidoarjo) - Isna Fitria Agustina (Universitas Muhammadiyah Sidoarjo, 2016)
The purposes of this research described the implementation of the strategic development of the strategic agropolitan area in Jabon district Sidoarjo and described the factors that become an obstacle in the implementation of poverty alleviation social. This study used a qualitative method with descriptive data approach, to gather information through interviews, observation and document analysis. Data analysis is performed with data reduction, presentation and conclusion. The conclusion of this study emphasized that there are two important factors that indicate the results of the development of strategic areas agropolitan such as supporting poverty reduction is still less than optimal. This happens due to several factors namely sub-systems such as the development of agricultural resources and competitive commodities, public facilities and infrastructure, social and agribusiness are required for a support haven’t been provided by the local government to the village administration in the region Jabon. Second the inhibiting factor both government and society itself. The services provided by the district governments do not make the people satisfied besides the communication between the government districts and communities do not occur regularly. In this case, their lack of knowledge and information on how the resource is used as a tool of social poverty alleviation. This happens because the level of public education remains low and access in the process of fulfilling the knowledge and information is still limited.